Self-healing coating capable of automatically repairing tiny scratches and preparation method thereof
By adding specific components such as talc, mica and photothermal fillers to the paint, the problem of poor scratch resistance and self-healing performance of existing paints is solved, and the automatic repair function of self-healing paints is realized, which improves its Scratch resistance and self-healing effect.
Patent Information
- Application Number
- CN202411759253.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-02
AI Technical Summary
There are few wall coatings on the existing market that can resist scratches and self-healing, and their scratches and self-healing properties are not ideal.
By adding talc, mica, photothermal filler and polymer aggregate to the coating, the ratio of resin and solvent is optimized to form a self-healing coating that can automatically repair tiny scratches.
It realizes that the paint can be automatically repaired after being subjected to tiny scratches, improves the scratch resistance and self-healing properties of the paint, so that it can absorb and store heat under sunlight, and increases the coating temperature for self-healing.
Smart Images

Figure BDA0005167660360000071 
Figure BDA0005167660360000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of self-healing coatings, and in particular to a self-healing coating capable of automatically repairing tiny scratches and a preparation method thereof. Background Art
[0002] Paint is a material that is applied to the surface of an object to be protected or decorated and can form a continuous film that is firmly attached to the object. This material is usually a viscous liquid made of resin, oil, emulsion, with or without pigments, fillers, and corresponding additives, and is prepared with organic solvents or water.
[0003] In recent years, a large number of paints with scratch resistance have appeared in the paint industry, but they basically achieve scratch resistance by increasing the hardness of the paint film and enhancing the smoothness of the paint film surface. However, there are relatively few wall paints on the market that are both scratch-resistant and self-healing, and their scratch resistance and self-healing properties are not ideal. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a self-healing coating capable of automatically repairing tiny scratches and a preparation method thereof.
[0005] The object of the present invention is to provide a self-healing coating that can automatically repair tiny scratches. The raw materials for preparing the self-healing coating include resin and solvent, wherein, calculated by weight ratio, the resin: the solvent = (8-10): 1;
[0006] The resin comprises the following components in parts by weight: 20-30 parts of epoxy resin, 30-50 parts of polyimide resin, 2-4 parts of red iron oxide, 20-30 parts of talc powder, 15-25 parts of mica powder, 10-20 parts of photothermal filler, and 30-50 parts of polymer aggregate;
[0007] The solvent comprises the following components in parts by weight: 100-200 parts of tetrahydrofuran, 5-10 parts of azobisisobutyronitrile, 10-15 parts of a diluent, 3-5 parts of polydimethylsiloxane, and 10-20 parts of an endothermic solvent.
[0008] The self-healing coating provided by the present invention improves the scratch resistance of the coating by adding talcum powder and mica powder. The lubricity and flow-aiding property of talcum powder help the mica powder to be evenly distributed in the coating; at the same time, the hardness and toughness of mica powder can make up for the low hardness of talcum powder. In addition, the layered structure of talcum powder and mica powder enables them to form a dense protective film in the coating, which helps to resist scratches and scrapes from the outside and improves the scratch resistance of the coating.
[0009] Preferably, the raw materials of the photothermal filler include ferroferric oxide and carbon black; and the weight ratio of ferroferric oxide to carbon black is (2-4):(3-5).
[0010] The self-healing coating provided by the present invention improves the heat absorption and heat-solidification properties of the coating by adding a photothermal filler. The photothermal filler is prepared by combining ferroferric oxide and carbon black, both of which have a certain light absorption capacity and can convert light energy into heat energy. Through photothermal conversion, this combination can effectively increase the temperature of the coating, thereby achieving temperature regulation.
[0011] Preferably, the polymer aggregate raw material includes dopamine methacrylamide and methacryloxypropyl dimethylmethoxysilane; and the weight ratio of dopamine methacrylamide to methacryloxypropyl dimethylmethoxysilane is 1:(2-4).
[0012] The self-healing coating provided by the present invention adds a polymer aggregate prepared from dopamine methacrylamide and methacryloxypropyl dimethylmethoxysilane to achieve the repair of tiny scratches and achieve a self-healing effect. The photothermal filler and heat-absorbing solvent added to the self-healing coating have good heat absorption and solid heat properties, so that the self-healing coating can absorb and store heat under the irradiation of sunlight to increase the temperature of the coating. Dopamine methacrylamide and methacryloxypropyl dimethylmethoxysilane can undergo free radical polymerization at high temperatures to generate a graft copolymer. This copolymer has autonomous self-repairing ability and is an intrinsic self-repairing material. Among them, methacryloxypropyl dimethylmethoxysilane, as a flexible segment, can increase the mobility of dopamine methacrylamide, and the hydrogen bonds in dopamine methacrylamide are the key to self-repair. When the coating is damaged by tiny scratches, these hydrogen bonds can be reformed to achieve the repair of the scratches.
[0013] Preferably, the diluent raw material includes allyl glycidyl ether and polyester modified acrylate; and the weight ratio of allyl glycidyl ether to polyester modified acrylate is (1-3): (2-4).
[0014] Preferably, the endothermic solvent raw material comprises ammonium nitrate solution, ammonium chloride solution and potassium nitrate solution; and the weight ratio of the ammonium nitrate solution, the ammonium chloride solution and the potassium nitrate solution is (3-6): (1-3): (2-4).
[0015] The self-healing coating provided by the present invention improves the heat absorption performance of the coating by adding a heat absorption solvent. The heat absorption solvent is prepared from ammonium nitrate solution, ammonium chloride solution and potassium nitrate solution. These three solvents themselves have good heat absorption performance. The combination of the three makes the heat absorption performance produce a superposition effect, which can absorb more heat and is applied to the preparation process of the coating to improve the heat absorption performance of the coating.
[0016] Another object of the present invention is to provide a method for preparing a self-healing coating capable of automatically repairing tiny scratches, comprising the following steps:
[0017] S1, mixing the epoxy resin and the polyimide resin, heating and stirring, cooling to room temperature, adding the talcum powder, the mica powder, the red iron oxide, the photothermal filler and the polymer aggregate, stirring evenly, grinding, and obtaining a resin;
[0018] S2, mixing the tetrahydrofuran, the azobisisobutyronitrile and the polydimethylsiloxane, heating and stirring evenly, cooling to room temperature, adding the diluent and the endothermic solvent and stirring in vacuum to obtain a mixture A;
[0019] S3. Mix the resin described in step S1 and the mixture A described in step S2, and stir them evenly to obtain a self-healing coating.
[0020] Preferably, the heating temperature in step S1 is 900-1200° C., and the heating time is 2-3 hours.
[0021] Preferably, the heating temperature in step S2 is 1500-2000° C., and the heating time is 3-5 hours. DETAILED DESCRIPTION
[0022] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0023] Example 1
[0024] This embodiment provides a self-healing coating that can automatically repair tiny scratches. The self-healing coating is prepared by the following steps:
[0025] 1. Raw material preparation:
[0026] Resin: 20 parts of epoxy resin, 30 parts of polyimide resin, 2 parts of red iron oxide, 20 parts of talcum powder, 15 parts of mica powder, 10 parts of photothermal filler, 30 parts of polymer aggregate;
[0027] Solvent: 100 parts of tetrahydrofuran, 5 parts of azobisisobutyronitrile, 10 parts of diluent, 3 parts of polydimethylsiloxane, and 10 parts of endothermic solvent.
[0028] 2. Preparation of self-healing coatings:
[0029] S1, mixing the epoxy resin and the polyimide resin, heating and stirring, cooling to room temperature, adding the talcum powder, the mica powder, the red iron oxide, the photothermal filler and the polymer aggregate, stirring evenly, grinding, and obtaining a resin;
[0030] S2, mixing the tetrahydrofuran, the azobisisobutyronitrile and the polydimethylsiloxane, heating and stirring evenly, cooling to room temperature, adding the diluent and the endothermic solvent and stirring in vacuum to obtain a mixture A;
[0031] S3. Mix the resin described in step S1 and the mixture A described in step S2, and stir them evenly to obtain a self-healing coating.
[0032] The weight ratio of the resin to the solvent is 8:1.
[0033] Among them, the photothermal filler is prepared from ferroferric oxide and carbon black, and the weight ratio of ferroferric oxide microbodies to carbon black is 2:3.
[0034] Wherein, the polymer aggregate is prepared from dopamine methacrylamide and methacryloxypropyl dimethylmethoxysilane, and the weight ratio of dopamine methacrylamide to methacryloxypropyl dimethylmethoxysilane is 1:2.
[0035] The diluent is prepared from allyl glycidyl ether and polyester modified acrylate, wherein the weight ratio of allyl glycidyl ether to polyester modified acrylate is 1:2.
[0036] The endothermic solvent consists of ammonium nitrate solution, ammonium chloride solution and potassium nitrate solution, and the weight ratio of the ammonium nitrate solution, the ammonium chloride solution and the potassium nitrate solution is 3:1:2.
[0037] Wherein, the heating temperature in step S1 is 900° C. and the heating time is 2 h.
[0038] Wherein, the heating temperature in step S2 is 1500° C. and the heating time is 3 hours.
[0039] Example 2
[0040] This embodiment provides a self-healing coating that can automatically repair tiny scratches. The self-healing coating is prepared by the following steps:
[0041] 1. Raw material preparation:
[0042] Resin: 25 parts of epoxy resin, 40 parts of polyimide resin, 3 parts of red iron oxide, 25 parts of talc powder, 20 parts of mica powder, 15 parts of photothermal filler, 40 parts of polymer aggregate;
[0043] Solvent: 150 parts of tetrahydrofuran, 7 parts of azobisisobutyronitrile, 13 parts of diluent, 4 parts of polydimethylsiloxane, and 15 parts of endothermic solvent.
[0044] 2. Preparation of self-healing coatings:
[0045] S1, mixing the epoxy resin and the polyimide resin, heating and stirring, cooling to room temperature, adding the talcum powder, the mica powder, the red iron oxide, the photothermal filler and the polymer aggregate, stirring evenly, grinding, and obtaining a resin;
[0046] S2, mixing the tetrahydrofuran, the azobisisobutyronitrile and the polydimethylsiloxane, heating and stirring evenly, cooling to room temperature, adding the diluent and the endothermic solvent and stirring in vacuum to obtain a mixture A;
[0047] S3. Mix the resin described in step S1 and the mixture A described in step S2, and stir them evenly to obtain a self-healing coating.
[0048] The weight ratio of the resin to the solvent is 9:1.
[0049] Among them, the photothermal filler is prepared from ferroferric oxide microparticles and carbon black, and the weight ratio of ferroferric oxide microparticles to carbon black is 3:4.
[0050] Wherein, the polymer aggregate is prepared from dopamine methacrylamide and methacryloxypropyl dimethylmethoxysilane, and the weight ratio of dopamine methacrylamide to methacryloxypropyl dimethylmethoxysilane is 1:3.
[0051] The diluent is prepared from allyl glycidyl ether and polyester modified acrylate, wherein the weight ratio of allyl glycidyl ether to polyester modified acrylate is 2:3.
[0052] The endothermic solvent consists of ammonium nitrate solution, ammonium chloride solution and potassium nitrate solution, and the weight ratio of the ammonium nitrate solution, the ammonium chloride solution and the potassium nitrate solution is 5:2:3.
[0053] Wherein, the heating temperature in step S1 is 1050° C. and the heating time is 2.5 h.
[0054] Wherein, the heating temperature in step S2 is 1750° C. and the heating time is 4 hours.
[0055] Example 3
[0056] This embodiment provides a self-healing coating that can automatically repair tiny scratches. The self-healing coating is prepared by the following steps:
[0057] 1. Raw material preparation:
[0058] Resin: 30 parts of epoxy resin, 50 parts of polyimide resin, 4 parts of red iron oxide, 30 parts of talc, 25 parts of mica powder, 20 parts of photothermal filler, 50 parts of polymer aggregate;
[0059] Solvent: 200 parts of tetrahydrofuran, 10 parts of azobisisobutyronitrile, 15 parts of diluent, 5 parts of polydimethylsiloxane, and 20 parts of endothermic solvent.
[0060] 2. Preparation of self-healing coatings:
[0061] S1, mixing the epoxy resin and the polyimide resin, heating and stirring, cooling to room temperature, adding the talcum powder, the mica powder, the red iron oxide, the photothermal filler and the polymer aggregate, stirring evenly, grinding, and obtaining a resin;
[0062] S2, mixing the tetrahydrofuran, the azobisisobutyronitrile and the polydimethylsiloxane, heating and stirring evenly, cooling to room temperature, adding the diluent and the endothermic solvent and stirring in vacuum to obtain a mixture A;
[0063] S3. Mix the resin described in step S1 and the mixture A described in step S2, and stir them evenly to obtain a self-healing coating.
[0064] The weight ratio of the resin to the solvent is 10:1.
[0065] Among them, the photothermal filler is prepared from ferroferric oxide microparticles and carbon black, and the weight ratio of ferroferric oxide microparticles to carbon black is 4:5.
[0066] Wherein, the polymer aggregate is prepared from dopamine methacrylamide and methacryloxypropyl dimethylmethoxysilane, and the weight ratio of dopamine methacrylamide to methacryloxypropyl dimethylmethoxysilane in the polymer aggregate is 1:4.
[0067] The diluent is prepared from allyl glycidyl ether and polyester modified acrylate, wherein the weight ratio of allyl glycidyl ether to polyester modified acrylate is 3:4.
[0068] The endothermic solvent consists of ammonium nitrate solution, ammonium chloride solution and potassium nitrate solution, and the weight ratio of the ammonium nitrate solution, the ammonium chloride solution and the potassium nitrate solution is 6:3:4.
[0069] Wherein, the heating temperature in step S1 is 1200° C. and the heating time is 3 hours.
[0070] Wherein, the heating temperature in step S2 is 2000° C. and the heating time is 2 h.
[0071] Example 4
[0072] This embodiment provides a self-healing coating that can automatically repair tiny scratches. Compared with Example 1, the difference in structure is that the photothermal filler is only prepared from ferroferric oxide. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0073] Example 5
[0074] This embodiment provides a self-healing coating that can automatically repair tiny scratches. Compared with Example 1, the difference in structure is that the endothermic solvent is prepared only from ammonium nitrate solution. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0075] Example 6
[0076] This embodiment provides a self-healing coating that can automatically repair tiny scratches. Compared with Example 1, the difference in structure is that the polymer aggregate is prepared only from dopamine methacrylamide. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0077] Example 7
[0078] This embodiment provides a self-healing coating that can automatically repair tiny scratches. Compared with Example 1, the difference in structure is that the diluent is prepared from allyl glycidyl ether only. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0079] Test Case
[0080] The self-healing coatings prepared in Examples 1-7 were selected for coating tests, and the wall facade was used as the coating surface. The experiment was carried out outdoors, and after the coating was completely dry, a coin was used to scrape the surface for 1 minute. The outdoor experimental environment should keep the coating surface ventilated, and the three coatings should be separated by 1.2-1.5m. The experimental temperature should be maintained at the normal outdoor temperature. The final test results are shown in Table 1.
[0081] Table 1 Test results of self-healing coatings
[0082]
[0083]
[0084] The self-healing coatings of Example 1, Example 2 and Example 3 all showed good scratch repair performance within 72 hours after application, and the scratches basically disappeared. This shows that the ratio and interaction between the components such as resins, solvents, photothermal fillers, polymer aggregates, etc. in these coatings are effective, and can realize the function of automatically repairing tiny scratches. The self-healing coatings of Example 4, Example 5, Example 6 and Example 7 did not have as good scratch repair effects as Examples 1, 2, and 3 within 72 hours after application, and the scratches were only slightly faded. This may be due to changes in the formulation of these coatings, such as changes in the type and proportion of photothermal fillers, endothermic solvents or polymer aggregates, which affected the self-healing properties of the coatings. The common facade coatings on the market still had obvious and clear scratches within 72 hours after application, and did not show any self-healing properties.
[0085] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A self-healing coating capable of automatically repairing tiny scratches, characterized in that: The raw materials for preparing the self-healing coating include resin and solvent, wherein, calculated by weight ratio, the resin: the solvent = (8-10): 1; The resin comprises the following components in parts by weight: 20-30 parts of epoxy resin, 30-50 parts of polyimide resin, 2-4 parts of red iron oxide, 20-30 parts of talc powder, 15-25 parts of mica powder, 10-20 parts of photothermal filler, and 30-50 parts of polymer aggregate; The solvent comprises the following components in parts by weight: 100-200 parts of tetrahydrofuran, 5-10 parts of azobisisobutyronitrile, 10-15 parts of a diluent, 3-5 parts of polydimethylsiloxane, and 10-20 parts of an endothermic solvent.
2. The self-healing coating according to claim 1, characterized in that The photothermal filler raw materials include ferroferric oxide and carbon black; and the weight ratio of ferroferric oxide to carbon black is (2-4): (3-5).
3. The self-healing coating according to claim 1, characterized in that: The polymer aggregate raw material comprises dopamine methacrylamide and methacryloxypropyl dimethylmethoxysilane; and the weight ratio of dopamine methacrylamide to methacryloxypropyl dimethylmethoxysilane is 1:(2-4).
4. The self-healing coating according to claim 1, characterized in that: The diluent raw material includes allyl glycidyl ether and polyester modified acrylate; and the weight ratio of allyl glycidyl ether to polyester modified acrylate is (1-3): (2-4).
5. The self-healing coating according to claim 1, characterized in that: The endothermic solvent raw materials include ammonium nitrate solution, ammonium chloride solution and potassium nitrate solution; and the weight ratio of the ammonium nitrate solution, the ammonium chloride solution and the potassium nitrate solution is (3-6): (1-3): (2-4).
6. A method for preparing the self-healing coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, mixing the epoxy resin and the polyimide resin, heating and stirring, cooling to room temperature, adding the talcum powder, the mica powder, the red iron oxide, the photothermal filler and the polymer aggregate, stirring evenly, grinding, and obtaining a resin; S2, mixing the tetrahydrofuran, the azobisisobutyronitrile and the polydimethylsiloxane, heating and stirring evenly, cooling to room temperature, adding the diluent and the endothermic solvent and stirring in vacuum to obtain a mixture A; S3. Mix the resin described in step S1 and the mixture A described in step S2, and stir them evenly to obtain a self-healing coating.
7. The preparation method according to claim 6, characterized in that: The heating temperature in step S1 is 900-1200° C. and the heating time is 2-3 hours.
8. The preparation method according to claim 6, characterized in that: The heating temperature in step S2 is 1500-2000° C. and the heating time is 3-5 hours.
Citation Information
Patent Citations
Thermal-response high-polymer self-healing coating and preparation method thereof
CN110240847A
Sunlight-driven self-repairing coating, coating layer, and preparation method of coating layer
CN113861800A